(untitled) (Periphērica, 2020)
The Flower of My Secret (1995) stands out as one of the least cited films in Pedro Almodóvar’s filmography. This absence of critical attention contrasts with the care that the director put into the construction of its characters and the consideration he paid to each of the details that made up this melodrama. The flower of my secret keeps many of Almodóvar’s usual traits, but with a particular tone that makes this film a defining moment in his career, since it marks a transition in his creative process, it constitutes a before and an after in his filmic production. In this essay I analyze the trope of creation in The Flower of My Secret and explain the reasons why this film could be considered Almodóvar’s most metafictional work, since it reflects on each of the elements that are part of his creative universe. The film is an eulogy to the process of both literary and cinematographic creation in the format of a melodrama; the viewer travels, in 103 minutes, across the tropes that constitute the Almodovarian universe, either explicitly or through allusion. The film pays tribute to its name.